Análise da estrutura genética populacional de duas espécies de Characiformes (Pygocentrus nattereri e Potamorhina latior) na região da bacia do Rio Madeira, Rondônia - Marín, Jorge Mori [UNESP] (2013)
The order Characiformes gathers approximately 1,670 freshwater species, of which at least 1,300 occur in Brazil. To date relatively few genetic studies have been conducted with species of this group, particularly in the Amazon. An important question for the moment is whether there is some isolation between local populations separated by rapids or fast in the Amazon, given the hydroelectric potential estimated for these environments. Accordingly, in this study, conducted under the Conservation Program Ichthyofauna of Santo Antônio Energia, were evaluated two local populations of two species: Pygocentrus nattereri and Potamorhina latior. We employ sequences of the control region (D-loop) of the mitochondrial DNA, the higher rate of this gene mutation present in relation to other genes. The samples were taken upstream and downstream of the old waterfall Teotônio to test the hypothesis that this waterfall served as a barrier for these species. Were examined 54 specimens of P. nattereri (25 upstream and 29 downstream) and 45 of P. latior (25 upstream and 20 downstream). The results showed that the amount of specimens of P. nattereri have greater genetic variability (Haplotypes = 5, Hd = 0607, π = 0.00105) that the downstream (Haplotypes = 2, Hd = 0379, π = 0.00046). In the case of P. latior, these values were similar both upstream (Haplotypes = 23, Hd = 0993, π = 0.01232) and downstream (Haplotypes = 17, Hd = 0.984, π = 0.01865). Both species have shared haplotypes in the two localities. The genetic divergence between the localities of P. nattereri (0.1%) was lower than in P. latior (1.9%). The analysis of molecular variance revealed significant differences between the localities of P. nattereri (Φst = 0.11448, P = 0.018) and P. latior (Φst = 0.16408, P = 0.000). The results suggest that a possible population structure existed between the two localities sampled both by differences in genetic variability as well as by allelic ...